2017
DOI: 10.3389/fpsyg.2017.00594
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Children's Ability to Read Children's and Adults' Mental States in an Adaptation of the Reading the Mind in the Eyes Task

Abstract: The ability to read mental states from subtle facial cues is an important part of Theory of Mind, which can contribute to children's daily life social functioning. Mental state reading performance is influenced by the specific interactions in which it is applied; familiarity with characteristics of these interactions (such as the person) can enhance performance. The aim of this research is to gain insight in this context effect for mental state reading in children, assessed with the Reading the Mind in the Eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
0
14
1
Order By: Relevance
“…Previously, studies have shown that females have better social cognition, 22 but other studies did not detect any difference between the genders. 27 , 28 Research has shown that this situation may vary according to their diagnosis, socioeconomic status, and age group. 6 , 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, studies have shown that females have better social cognition, 22 but other studies did not detect any difference between the genders. 27 , 28 Research has shown that this situation may vary according to their diagnosis, socioeconomic status, and age group. 6 , 27 …”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 Research has shown that this situation may vary according to their diagnosis, socioeconomic status, and age group. 6 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…A sample size calculation was used to determine the minimum number of participants needed for this pilot study, which intended to explore the mediating contribution of cRMET to the relationship between ADHD and CUt. Previous studies have demonstrated an adequate test–retest reliability (Van der Meulen et al, 2017) and low to moderate internal reliability for overall task accuracy in cRMET (Girli, 2014; Kittel et al, 2021; Vellante et al, 2013). Its internal reliability in the current study, measured by Cronbach’s α, was 0.63, supporting the possibility that FER modeled by cRMET is not unidimensional (Kittel et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The electronic tests were supplemented with 3 well-validated pencil and paper tests from the Wechsler Intelligence Scale for Children - Fifth Edition 39 (Digit Span Forward & Backward) and Delis Kaplan Executive Function System 41 (FAS Letter Fluency), as well as the parental report Prospective and Retrospective Memory Questionnaire for Children (PRMQ) 40 . In session 2, a novel inclusion was the assessment of social cognition using the Children’s Reading Mind in the Eyes Task (RME) 45 and the Empathy Questionnaire for Children and Adolescents (EmQue-CA) 44 , along with the viewing of the Partly Cloudy movie to capture both cognitive and affective Theory of Mind while in the scanner (described in detail above). In addition, we obtained consent to access their National Assessment Program – Literacy and Numeracy (NAPLAN) scores (https://www.nap.edu.au/home).…”
Section: Methodsmentioning
confidence: 99%
“…Pediatric Daytime Sleepiness Scale (PDSS) 67   Sleep Disturbances Scale for Children (SDSC) 68  Sleep behaviours across early childhood -items adapted from Generation R Experiences and worries ‡   Active and Passive Social Media Use (APSMU) 74,75  UCLA Brief COVID-19 Screen for Child/Adolescent PTSD (PTSD) 76  Perceived Stress Scale (PSS) 77  Brief Resilience Scale (BRS) 78   well as the parental report Prospective and Retrospective Memory Questionnaire for Children (PRMQ) 42 . In session 2, a novel inclusion was the assessment of social cognition using the Children's Reading Mind in the Eyes Task (RME) 45 and the Empathy Questionnaire for Children and Adolescents (EmQue-CA) 44 , along with the viewing of the Partly Cloudy movie to capture both cognitive and affective Theory of Mind while in the scanner (described in detail above). In addition, we obtained consent to access their National Assessment Program -Literacy and Numeracy (NAPLAN) scores (https://www.nap.edu.au/home).…”
Section: Sleep and Physical Healthmentioning
confidence: 99%